Pelatihan Manajemen Olahraga Bola Voli bagi Pelatih di Kabupaten Sleman - Sujarwo Sujarwo; Nurhadi Santoso; Abdul Mahfudin Alim (Universitas PGRI Semarang, 2023)
The game of volleyball is the number one sport of choice in society, therefore this sport needs to be packaged properly. The purpose of this community service is to provide education to volleyball coaches in Sleman district about volleyball sports management. Methods of community service with lectures and direct discussions. The target audience for this community service are 20 volleyball coaches. The expected knowledge from the results of this service is that activity participants have increased knowledge about volleyball sport management. Place of dedication at the